Preparation of Mesoporous SnO2 by Electrostatic Self-Assembly - Yang Jing; Wang Yan; Xu Xiaowen (Journal of Chemistry)
We report a simple and scalable strategy to synthesize mesoporous SnO2 with tin dioxide nanoparticles of 5-6 nm crystalline walls and 3-4 nm pore diameter with the assistance of Mo7O246- as templating agent at room temperature. The samples were characterized by XRD, TEM, UV-DRS, XPS, and BET. The product has a moderately high surface area of 132 m2 g−1 and a narrow mesoporous structure with an average pore diameter of 3.5 nm. The photocatalytic activities of the mesoporous SnO2 were evaluated by the degradation of methyl orange (MO) in aqueous solution under UV light irradiation.